2022
DOI: 10.1126/sciadv.abn8614
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of hybrid spheroids of mesenchymal stem cells and drug depots for immunomodulating effect in islet xenotransplantation

Abstract: Immunomodulation is an essential consideration for cell replacement procedures. Unfortunately, lifelong exposure to nonspecific systemic immunosuppression results in immunodeficiency and has toxic effects on nonimmune cells. Here, we engineered hybrid spheroids of mesenchymal stem cells (MSCs) with rapamycin-releasing poly(lactic- co -glycolic acid) microparticles (RAP-MPs) to prevent immune rejection of islet xenografts in diabetic C57BL/6 mice. Hybrid spheroids were rapidly formed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…A previous study showed that syngeneic MSCs can be rejected as early as 7 days after injection . We have recently demonstrated that co-injection of syngeneic MSCs with an immunosuppressive drug depot can improve MSC retention in the injected site for around 3–4 weeks . Given that DEXA is a potent immunosuppressive drug, we expect that this drug delivery system could protect syngeneic MSCs for certain time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A previous study showed that syngeneic MSCs can be rejected as early as 7 days after injection . We have recently demonstrated that co-injection of syngeneic MSCs with an immunosuppressive drug depot can improve MSC retention in the injected site for around 3–4 weeks . Given that DEXA is a potent immunosuppressive drug, we expect that this drug delivery system could protect syngeneic MSCs for certain time.…”
Section: Discussionmentioning
confidence: 99%
“…52 We have recently demonstrated that co-injection of syngeneic MSCs with an immunosuppressive drug depot can improve MSC retention in the injected site for around 3−4 weeks. 7 Given that DEXA is a potent immunosuppressive drug, we expect that this drug delivery system could protect syngeneic MSCs for certain time. Currently, our data showed clear improvement in new bone formation after implantation of the MFS loaded with PD-DEXA/MP-conjugated spheroids at 4 weeks, but the new bone did not completely fill the defect at 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations